-3(1+h)=.33(3-12h)

Simple and best practice solution for -3(1+h)=.33(3-12h) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(1+h)=.33(3-12h) equation:


Simplifying
-3(1 + h) = 0.33(3 + -12h)
(1 * -3 + h * -3) = 0.33(3 + -12h)
(-3 + -3h) = 0.33(3 + -12h)
-3 + -3h = (3 * 0.33 + -12h * 0.33)
-3 + -3h = (0.99 + -3.96h)

Solving
-3 + -3h = 0.99 + -3.96h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '3.96h' to each side of the equation.
-3 + -3h + 3.96h = 0.99 + -3.96h + 3.96h

Combine like terms: -3h + 3.96h = 0.96h
-3 + 0.96h = 0.99 + -3.96h + 3.96h

Combine like terms: -3.96h + 3.96h = 0.00
-3 + 0.96h = 0.99 + 0.00
-3 + 0.96h = 0.99

Add '3' to each side of the equation.
-3 + 3 + 0.96h = 0.99 + 3

Combine like terms: -3 + 3 = 0
0 + 0.96h = 0.99 + 3
0.96h = 0.99 + 3

Combine like terms: 0.99 + 3 = 3.99
0.96h = 3.99

Divide each side by '0.96'.
h = 4.15625

Simplifying
h = 4.15625

See similar equations:

| x-2y+z=4 | | 38=17-y | | -36+24-3=y | | 9x^2-1=80 | | 80y=4w+5x | | x-2y+4=4 | | 140n^3+40n^2-35n-10=0 | | 17=9y | | 4(2x-3)-3(5x+4)=7x(5x-4) | | x+x^2+1=0 | | 6x+52=2x+88 | | -.2f+.8f+21=6 | | 6.7a+15=82 | | 53.7q+1.2=386.2-1.3q | | sqrt(u-5)=6 | | 5.44=.34a | | 5(3x-7)-7=5(x-2)+28 | | -6250+(4x)=-10 | | 12x^2-52x+80=0 | | 2x=x^2-6x+7 | | 50v^3+10v^2-40v-8=0 | | 5x+5=3x+19 | | x^2+7x+10=180 | | .2f+.8f+21=6 | | 5x+37=7x+47 | | x^3-3x^2+2x=60 | | 45=4x+15 | | 7a^2x^2+4ax-8=0 | | 17x-4=180 | | .8(g+15)=24 | | 23=1-4x+6 | | 9x+42x+49=0 |

Equations solver categories